Bioprospecting of Lactobacillus sp. Starter Culture from Colostrum Breast Milk for Probiotic Milk Production from Soybeans - Rahmah, Mufti Hatur; Masriany, Masriany; Ramlah, Ramlah; Isdaryanti, Isdaryanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Lactobacillus sp. is a bacterium that naturally exists in various environments, including in breast milk colostrum. This bacterium belongs to a group of lactic acid bacteria that produce lactic acid as the main product of sugar fermentation so that it has probiotic properties that also play a role in the fermentation process. This study aims to produce probiotic milk using Lactobacillus sp isolates from breast milk colostrumÂ  with soybean (Glycine max (L.) Merril.) as the base material and then test the total lactic acid content, pH value, reducing sugar and the number of lactic acid bacteria. The production of soybean fermented milk is based on the analysis of total lactic acid content by acid-base titration method with 0.1 N NaOH standard solution, pH value by using universal pH meter, reducing sugar test by spectrophotometric method of Nelson-Somogyi and the number of lactic acid bacteria by using Glucose Yeast Pepton Agar (GYPA) medium added with CaCO3 then calculated by using Standard Plate Count (SPC) method with TPC value (Total Plate Number) is 2.3. 1012 colonies/ml, 2.5.1012 colonies/ml, 4.5.1014 colonies/ml, 4.1.1014 colonies/ml. From the results of the study it is known that Lactobacillus sp isolates from breast milk colostrum fluid can ferment soybean milk (Glycine max (L.) Merril.)